Morphometric Studies of Seagrass Halophila ovalis (R.Brown) Hooker in Kahona, Lembeh Sub-district of Bitung City and in the Tasik Ria, Tombariri Sub-district , Minahasa District - Mizhael A.P. Wulur; Khrsitin I. F. Kondoy; Jety K. Rangan (Sam Ratulangi University, 2019)
Seagrass is a marine plant that has roots with a rhizom system, the structure of the stem and leaves can be clearly distinguished. Halophila ovalis belongs to the Hydrocharitaceae family and common characteristics of this family include two branched leaves, oval leaf shape, small stalks and rhizomes that are easily broken and smooth, single-haired roots. This research was carried out in the coastal waters of Kahona Beach, South Lembeh Sub-district, Bitung City, and in Tasik Ria Beach, Tombariri Sub-district, Minahasa Regency. To date, there is no information regarding the comparison of morphometric of seagrass Halophila ovalis in both locations. The research objective was to compare the morphometric size of Halophila ovalis based on both research locations (Kahona Beach and Tasik Ria Beach). Data collection was conducted using survey method. As many as 30 plants in each study location were collected, washed with sea water and put into plastic samples which would then be measured using a digital caliper.In the results obtained, statistically, the Halophila ovalis species on Kahona Beach and Tasik Ria Beach are the same. There is no significant difference with regard to the size of the growth. This is due to the condition of the existing environmental parameters. Environmental parameter conditions in these two locations are still within the safe limits of seagrasses to grow optimally. From the measurement results, it can be seen that the size of seagrass growth in Tasik Ria Beach is smaller than that on Kahona Beach. This is due to the activities of people who come touring that accidentally damage seagrasses and damaged coral reef ecosystems are unable to withstand the strong currents and trash carried. Whereas in Kahona Beach, this is a marine protected area that is still rare for tourists to visit even though it has become an ecotourism area so that the conditions are still good and maintained, not only the seagrass ecosystem but also mangrove ecosystems and coral reefs.Keywords: Morfometrics, Halophila ovalis, Kahona Beach, Tasik Ria BeachÂ ABSTRAKÂ Lamun adalah tumbuhan air yang memiliki akar dengan sistem perakaran rhizoma, struktur batang dan daun yang dapat dibedakan dengan jelas. Halophila ovalis termasuk dalam famili Hydrocharitaceae. Ciri-ciri umum dari famili ini antara lain daun bercabang dua, bentuk daun oval, memiliki tangkai yang kecil dan rhizome yang mudah patah serta akar tunggal yang berambut halus. Penelitian ini dilaksanakan di perairan Pantai Kahona Kecamatan Lembeh Selatan Kota Bitung dan di perairan Pantai Tasik Ria Kecamatan Tombariri Kabupaten Minahasa. Sampai saat ini, belum ada informasi mengenai perbandingan morfometrik lamun Halophila ovalis di kedua lokasi yang tersedia. Adapun yang menjadi tujuan penelitian yaitu membandingkan ukuran morfometrik Halophila ovalis berdasarkan lokasi penelititan (Pantai Kahona dan Pantai Tasik Ria). Pengambilan data dilakukan dengan menggunakan metode survei jelajah, sebanyak 30 pada setiap lokasi penelitian, dicuci dengan air laut dan dimasukan kedalam plastik sampel yang kemudian akan diukur dengan menggunakan caliper digital.Â Pada hasil yang diperoleh, secara statistik spesies Halophila ovalis di Pantai Kahona dan di Pantai Tasik Ria adalah sama. Tidak ada perbedaan yang nyata berkaitan dengan ukuran pertumbuhan tersebut. Hal ini disebabkan oleh kondisi parameter lingkungan yang ada. Kondisi parameter lingkungan pada kedua lokasi ini masih dalam batas yang aman bagi lamun untuk bertumbuh kembang secara optimal. Dari hasil pengukuran terlihat bahwa ukuran pertumbuhan lamun yang ada di Pantai Tasik Ria lebih kecil dari pada yang ada di Pantai Kahona. Hal ini disebabkan aktivitas masyarakat yang datang berwisata yang tidak sengaja merusak lamun serta ekosistem terumbu karang yang sudah rusak tidak mampu menahan kuatnya arus dan sampah yang terbawa. Sedangkan di Pantai Kahona ini merupakan daerah perlindungan laut yang masih jarang wisatawan walaupun sudah menjadi daerah ekowisata sehingga kondisi di Pantai Kahona masih baik dan terjaga, bukan hanya ekosistem lamunnya tapi juga ekosistem mangrove dan terumbu karang.Kata Kunci : Morfometrik, Halophila ovalis, Pantai Kahona, Pantai Tasik Ria